Transformacija sustava financiranja cestovne infrastrukture u Hrvatskoj - čimbenik racionalne infrastrukturne politike - Šimulčik, Damir (Promet - Traffic&Transportation, 2012)
Road infrastructure as an indispensable part of the community and economic life has a significant place in the area of a coordinated development of the process of simple and extended reproduction. This means that distortions in the segment of conceiving one consistent road infrastructure financing system procreate a variety of negative implications reflecting on the subsystem of road and overall economic system Thus the facilities of road infrastructure become an element of destabilization of the road system functioning as a subsystem of the economic life in Croatia maintaining with it a dynamic interactive relationship in the process of operation. The paper deals with the distortion of the financing system and the inevitability of its transformation within the scope of the restructuring of the Croatian economy. The basic prerequisite of the process of transformation rests in the rational functioning of the investment activity which should be complex, comprehensive and consistent, without any anemic, undeceive and declarative quality.